Ionising radiation: are orthopaedic surgeons at risk? - Smith, G; Briggs, T; Lavy, C; Nordeen, H (1992)
Modern orthopaedic trauma practice involves increased exposure of the surgeon to ionising radiation. However, there have been no studies to investigate whether the doses received are within limits for non-classified workers. In this study, whole body, eye and extremity, namely hand, doses were measured in six orthopaedic surgeons during trauma cases requiring the use of X-rays in theatre. None of the subjects approached the recommended maximum dose levels for either the whole body, eyes or hands. This finding is reassuring. In orthopaedics, the limiting dose is that to the hands. This differs from previously studied groups, such as radiologists and cardiologists, in whom the limiting factor is the dose to the lens of the eye. Although current precautions appear to be adequate, safe practice in the future will depend on continuing vigilance and repetition of studies similar to this one as techniques and workloads change.